A longitudinal corpus study of lexical bundles in students’ written and spoken narratives / Sharon Santhia John - Sharon Santhia , John (2019)
Phraseology in language use is said to be at the heart of language description (Sinclair, 1991; Hunston, 2002). Over the past 25 years there has been an upsurge in studies investigating phraseology in language use with corpus linguistics method and tools (Sinclair, 1991; Hunston 2002; Paquot & Granger, 2012). Yet, there is a lack of phraseological studies focusing on secondary school students of English (Ebeling & Hasselgård, 2015a). This study investigates the use of four-word lexical bundles based on structural and functional analysis in the written and spoken narrative texts of 42 students over a period of six months. The findings revealed that the use of lexical bundles in students’ written and spoken corpora seem to decrease over time. Structurally, the written and spoken narrative texts are dominated by verb phrase-based bundles followed by noun phrase/prepositional phrase-based bundles while functionally, referential expressions are most commonly used in the written and spoken narrative texts followed by topic-oriented expressions. The substantial use of referential expressions and minimal use of stance and discourse organizing bundles in the written and spoken narrative texts, despite the difference in the modes of production may indicate the possible requirement of the narrative genre that is descriptive in nature. Taken together the overall findings, complexity, inconsistency and dynamicity are observed within the written and spoken language of students as well as between the written and spoken language where divergent developmental paths are noted in both language use. The nature of language development is also observed to include developing towards specificity and a matter of choice of the students in making use of bundles with different structural forms for the same function in their written and spoken narrative texts.